Assessment of brain development in children with congenital diaphragmatic hernia: an automated brain segmentation approach - Mohamed, Sherif A.; Götz, Larissa; Saase, Victor; Elrod, Julia; Endlein, Jonathan Jürgen; Weis, Meike; Neumaier-Probst, Eva (In vivo, 2025)
Background/Aim: Congenital diaphragmatic hernia (CDH) is a critical condition affecting newborns, which often results in long-term morbidities, including neurodevelopmental delays, which affect cognitive, motor, and behavioral functions. These delays are believed to stem from prenatal and postnatal factors, such as impaired lung development and chronic hypoxia, which disrupt normal brain growth. Understanding the underlying mechanisms of these neurodevelopmental impairments is crucial for improving prognosis and patient outcomes, particularly as advances in treatments like ECMO have increased survival rates but also pose additional risks for neurodevelopment. This study aimed to evaluate brain development in 2-year-old children who underwent CDH repair, with and without ECMO, compared to healthy controls using an MRI-based automated segmentation approach. Patients and Methods: The study included 31 children with CDH, of which 10 received ECMO therapy, and a control group of 31 healthy children. MRI-examinations were performed using a 3-T system. MRI data were processed using the CerebroMatic toolbox and SPM12 software to measure cerebrospinal fluid (CSF), gray matter (GM), white matter (WM), and cortical thickness (CT). Results: Patients with CDH showed significantly increased volumes of CSF (p=0.009), GM (p=0.02), and total intracranial volume (TIV) (p=0.01), compared to healthy controls. ECMO-treated patients had significantly increased GM (p=0.01) and CSF (p=0.005) volumes in comparison to healthy controls. CT was significantly higher in CDH patients regardless of ECMO therapy, indicating potential maturational deficits. Conclusion: The study reveals neurodevelopmental differences in children with CDH, particularly in those requiring ECMO therapy. Increased CT, GM, and CSF volumes suggest complex neurodevelopmental challenges.